Design of Adaptive Planar Microstrip Patch Array Operating at 28 GHz for 5G Smart Mobile System - Rashid, Zhwan Mohammed; M. Jassim Al-Hindawi, Asaad (Kurdistan Journal of Applied Research, 2019)
Smart antenna system has been studied extensively for the fifth generation of wireless communication systems, because it has made a system better performance of higher capacity and coverage as well as of power-saving. The present paper introduces a design of planar microstrip patch antenna array for a smart mobile system operating at 28 GHz. The present smart antenna has an adaptive radiation pattern that adjusts its main beam automatically to the desired direction by following the signal environment. This is based on the processing of an algorithm called the Least Mean Square (LMS) resulting in a change in the magnitude and phase of the feeding current for each element in the antenna array. From the obtained results, the main beam can be steered 180 degrees in the phi (azimuth) plane at a constant theta (elevation) angle. The planar antenna array was designed and simulated using CST Microwave Studio and MATLAB software that is used to find the required exciting current for each element. It is found that the antenna bandwidth is greater than 1 GHz while its gain is about 21 dB.